Answer:
part (a) 46958.33 W
part (b) 43125 W
part (c) -57500 W
Step-by-step explanation:
Given,
- Mass of the car = m = 1150 kg
- Angle of inclination of the hill =
![\theta\ =\ 30^o](https://img.qammunity.org/2020/formulas/physics/college/9s9sig84yf0jpzgxy8bb0ym1d1a6bam7vn.png)
- Total time taken = t = 12 s
part (a)
Given that the velocity is constant,
Total displacement traveled by the car = s = 100 m
Work done by the car to reach at the top of the hill
![w\ =\ mgsin30^0* s\\\Rightarrow w\ =\ 1150* 9.81* sin30^o* 100\\\Rightarrow w\ =\ 563500\ J](https://img.qammunity.org/2020/formulas/physics/high-school/he6angu5i4tvokgnlwqxswb1ckbi9vbqm5.png)
Hence, power
![P \ =\ (w)/(t)\\\Rightarrow P\ =\ (563500)/(12)\\\Rightarrow P\ =\ 46958.33\ W](https://img.qammunity.org/2020/formulas/physics/high-school/qaqbls9m94m06qzp6a8exy6izhs7y677zy.png)
part (b)
Given,
- final velocity =
![v_f\ =\ 30\ m/s.](https://img.qammunity.org/2020/formulas/physics/high-school/kc9il2plazfgi9eepccw8y8gv3a3y03re1.png)
- Initial velocity =
![v_i\ =\ 0\ m/s](https://img.qammunity.org/2020/formulas/physics/high-school/6xieg38lg6ks64etwpoehcmq6sfwoeri4m.png)
Total power is equal to the ratio of the change in kinetic energy and total time taken
![\therefore P\ =\ (\Delta K.E)/(t)\\\Rightarrow P\ =\ (K.E_f\ -\ K.E_i)/(t)\\\Rightarrow P\ =\ ((1)/(2)mv_f^2\ -\ 0)/(t)\\\Rightarrow P\ =\ (mv_f^2)/(2t)\\\Rightarrow P\ =\ (1150* 30^2)/(2* 12)\\\Rightarrow P\ =\ 43125\ W](https://img.qammunity.org/2020/formulas/physics/high-school/18r2p66n5njhrk30ws0p3hz6lkxwimva9a.png)
part (c)
- Initial velocity of the car =
![v_i\ =\ 35\ m/s.](https://img.qammunity.org/2020/formulas/physics/high-school/qpyq30q18xmykgafxzzszh3mejwsijbxk6.png)
- Final velocity of the car =
![v_f\ =\ 5 m/s.](https://img.qammunity.org/2020/formulas/physics/high-school/vojuit763yb801ub394o195tg4a3hrb5dd.png)
Total power is equal to the ratio of the change in kinetic energy and total time taken
![\therefore P\ =\ (\Delta K.E)/(t)\\\Rightarrow P\ =\ (K.E_f\ -\ K.E_i)/(t)\\\Rightarrow P\ =\ ((1)/(2)mv_f^2\ -\ (1)/(2)mv_i^2)/(t)\\\Rightarrow P\ =\ (m(v_f^2\ -\ v_i^2))/(2t)\\\Rightarrow P\ =\ (1150* (5^2\ -\ 35^2))/(2* 12)\\\Rightarrow P\ =\ -57500\ W](https://img.qammunity.org/2020/formulas/physics/high-school/kr83y1l9fhembmrlu47lmk29pk5s171euw.png)